The effects of diabetes on attention function: a comparative analysis of children and adolescents with type 1 diabetes and their healthy peers - Wais, Paulina; Stanisławska-Kubiak, Maia; Niechciał, Elżbieta; Majewska, Katarzyna Anna; Wyrwas, Joanna; Mojs, Ewa; Fichna, Piotr; Kędzia, Andrzej (Frontiers in Endocrinology, 2025)
IntroductionManaging type 1 diabetes (T1D) is complex and requires frequent glucose monitoring, insulin dosing, and lifestyle adjustments to attain appropriate metabolic control. These self-management tasks demand intact cognitive and executive functions, particularly attention. Attention deficits in children and adolescents with T1D have been associated with poor metabolic control and an increased risk of complications. However, research into cognitive performance within this population remains limited. We evaluated attention abilities in children and adolescents with type 1 diabetes compared to healthy controls.Materials and MethodsThe study included 209 children (77 females), comprising 115 with T1D (54 females) and 94 healthy controls (23 females). The mean age of T1D patients was 12.95 years (SD 3.11), with an average disease duration of 5.22 years (SD 3.95). Cognitive functions were assessed using the MOXO Continuous Performance Test (MOXO-CPT), which evaluates attention-related parameters including sustained attention, reaction time, impulsivity, and hyperactivity. The relationship between cognitive performance and clinical parameters, including HbA1c level, treatment methods, glycemic monitoring, and disease duration, was analyzed.ResultsChildren with T1D demonstrated significantly lower sustained attention scores, slower reaction times, and worse hyperactivity levels than controls. Impulsivity did not differ significantly. Patients with HbA1c levels greater than 8% showed noticeably poorer attention performance. Gender, disease duration, treatment method, and type of glycemic monitoring were not associated with attention outcomes.ConclusionsChildren and adolescents with T1D exhibit worse neurocognitive performance, particularly in attention, compared to healthy peers. Poor metabolic control is linked to attention deficits. Routine cognitive screening of children and adolescents with T1D may enhance disease management and highlight the need for additional support in therapeutic tasks.